Le jardin des Viard ou les valeurs de la muséalisation - André Gob (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Musealisation, as a process incorporating a material object into the collection of a museum, lead to a status’alteration of this object. Several cases in different categories of museum are analysed to show that the cultural item gains a “museal value” wich is lacking in the case of private collection. The process of musealisation includes several operations: acquiring, documenting, preserving and often, it is concerned too with exhibition. Choices and values imbedded in this process are connected with the achievement of the mission statement of the museum.